The incorporation of Mg2+ ions into aragonite during biomineralization: Implications for the dolomitization of aragonite - Han, Zuozhen; Meng, Ruirui; Zhao, Hui; Gao, Xiao; Zhao, Yanyang; Han, Yu; Liu, Fang; Tucker, Maurice E.; Deng, Jiarong; Yan, Huaxiao (Frontiers in Microbiology, 2023)
Bacteria can facilitate the increase of Mg2+ content in biotic aragonite, but the molecular mechanisms of the incorporation of Mg2+ ion into aragonite facilitated by bacteria are still unclear and the dolomitization of aragonite grains is rarely reported. In our laboratory experiments, the content of Mg2+ ions in biotic aragonite is higher than that in inorganically-precipitated aragonite and we hypothesize that the higher Mg content may enhance the subsequent dolomitization of aragonite. In this study, biotic aragonite was induced by Bacillus licheniformis Y1 at different Mg/Ca molar ratios. XRD data show that only aragonite was precipitated in the media with Mg/Ca molar ratios at 6, 9, and 12 after culturing for 25 days. The EDS and atomic absorption results show that the content of Mg2+ ions in biotic aragonite increased with rising Mg/Ca molar ratios. In addition, our analyses show that the EPS from the bacteria and the organics extracted from the interior of the biotic aragonite contain the same biomolecules, including Ala, Gly, Glu and hexadecanoic acid. The content of Mg2+ ions in the aragonite precipitates mediated by biomolecules is significantly higher than that in inorganically-precipitated aragonite. Additionally, compared with Ala and Gly, the increase of the Mg2+ ions content in aragonite promoted by Glu and hexadecanoic acid is more significant. The DFT (density functional theory) calculations reveal that the energy needed for Mg2+ ion incorporation into aragonite mediated by Glu, hexadecanoic acid, Gly and Ala increased gradually, but was lower than that without acidic biomolecules. The experiments also show that the Mg2+ ion content in the aragonite significantly increased with the increasing concentration of biomolecules. In a medium with high Mg2+ concentration and with bacteria, after 2 months, micron-sized dolomite rhombs were precipitated on the surfaces of the aragonite particles. This study may provide new insights into the important role played by biomolecules in the incorporation of the Mg2+ ions into aragonite. Moreover, these experiments may contribute towards our understanding of the dolomitization of aragonite in the presence of bacteria.